Study on the factor that influence the abandoned housing project in Malaysia : mismanagement - Nur Fathin Nadhirah, Mohamad Noor (2017)
Abandonment of buildings has now becomes a serious problem especially to the development country. There were many buildings that was abandoned without completing it. The abandonment of development projects can be define as the act of discontinuing any activities or maintenance works on such development project within a time frame of the contract agreement and with no intention of returning back to the development. Besides that, the building can becomes abandoned when the location has experience a natural disaster, as a result, it become unsuitable for the project to be continued. When the project of the building has become abandoned, it can give an adverse effects on parties such as the developer, contractor, consultant and client. According to previous researchers, many factors cause the abandoned of projects such as the company’s management and financial problems. This study was conducted to investigate the factors that influence the abandonment of housing project in Malaysia cause by mismanagement by the developer and also to identify the suitable solution for the mismanagement problem occur in abandoned housing projects. In this study a set of questionnaire was distributed to the respondents come from constructions sector such as developer, consultant, construction and also public authorities. Foremost, the issues regarding the factor that cause abandoned housing projects were examined from the literature reviews. Then, questionnaire was prepared with 4 four sections, where Section A is respondent background while, Section B is respondents opinion regarding about abandoned housing project, Section C is the causes of mismanagement by the developer company and Section D for the suggestion of solutions regarding abandoned housing project. The 56 questionnaires were returned and analyzed. Then, the data collected was analyzed by using the Relative Importance Index (RII). From the result analysis, it shows that the main cause of mismanagement that contributes to the abandonment of the housing project is weakness in management of project by the inexperienced developer. The inexperience developer can lead the project to become delay and then abandoned. Developer will have an issue until it can affect the project such as financial crisis, issues with contractors and others.